The Influence of the Film “A Home for Alie” (2025) on the Formation of Moral Character in Adolescents - Prasetyo Adinugroho; Intan Tri Kusumaningtias; Restiawan Permana (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Film as a mass medium plays a crucial role as an agent of moral value socialization, especially for adolescents who are in the critical phase of identity formation. This study aims to measure the influence of the film "Rumah untuk Alie" (2025) on the moral character development of adolescents at Yayasan Sih Pakarti, Jakarta. The film raises realistic issues of family bullying and the resilience of the main character, which has the potential to become a moral exemplar. The study uses a quantitative approach with a causal-associative design. The research sample consisted of 100 respondents who are wards of Yayasan Sih Pakarti. Data were collected through research instruments and analyzed using descriptive statistics and simple linear regression test with the help of SPSS version 26 software. The results show that there is a positive and significant influence between watching the film "Rumah untuk Alie" and the moral character development of adolescents (t-count value 4,642 > t-table 1,997. The correlation coefficient (r) of 0.439 indicates a moderate relationship category, with a determination coefficient of 19%, meaning that the film contributes 19% to moral character development, while the remaining 81% is influenced by external factors. The most dominant moral character dimensions formed are empathy and social concern, followed by responsibility and honesty. This study concludes that family drama films with strong moral narratives have the potential to be effective as moral learning media for adolescents, especially in fostering sensitivity to bullying cases.